2015
DOI: 10.4067/s0717-95022015000200009
|View full text |Cite
|
Sign up to set email alerts
|

Histological Study of the Oesophagus and Stomach in Grey-Backed Shrike (Lanius tephronotus)

Abstract: ZHU, L. Histological study of the oesophagus and stomach in grey-backed shrike (Lanius tephronotus). Int. J. Morphol., 33(2):459-464, 2015. SUMMARY:The microstructure of oesophagus and stomach in grey-backed shrike were examined by means of light microscopy. The results showed that the oesophagus glands were mucous glands, the shedding glandular cells and the mucin from the oesophagus glands secreted to the lumen. The number of the glands in the thoracic part was less than that of in the cervical part. The lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 9 publications
6
19
0
Order By: Relevance
“…Many references refer to the nature of the food eaten by animal, and the way itis obtained will determine the histological structure of the digestive tract (4). The results showed that the stomach of the magpie was composed of two parts: proventiculus and gizzard, similar to many birds (8,9), while the stomach of the small asian mongoose consist of three regions: cardiac stomach, fundic stomach and pyloric stomach, which is consistent with (10). The stomach wall in both species consist of four main layers: mucosa, submucosa, muscularis externa and serosa.…”
Section: Discussionsupporting
confidence: 86%
“…Many references refer to the nature of the food eaten by animal, and the way itis obtained will determine the histological structure of the digestive tract (4). The results showed that the stomach of the magpie was composed of two parts: proventiculus and gizzard, similar to many birds (8,9), while the stomach of the small asian mongoose consist of three regions: cardiac stomach, fundic stomach and pyloric stomach, which is consistent with (10). The stomach wall in both species consist of four main layers: mucosa, submucosa, muscularis externa and serosa.…”
Section: Discussionsupporting
confidence: 86%
“…Histological results obtained in the present investigation revealed that the alimentary canal of Vanellus spinosus consists of four main layers; serosa, muscularis, submucosa and mucosa 9 . The oesophageal layers are three; serosa, muscularis and mucosa 10,11 . Muscularis layer is well developed and consists of two layers of muscle fibers; circular muscle fibers outwards and longitudinal muscle fibers inwards.…”
Section: Discussionmentioning
confidence: 99%
“…The muscularis is composed of outer longitudinal and inner circular muscle fibers 12,13 . The muscularis is formed of circular muscle layer in their studies on germain's swiftlet and Grey-Backed Shrike respectively 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal muscularis mucosa an extension of muscle lying close to the mucosal glands might be responsible for putting pressure on the glands resulting in contraction to release mucin [22]. Thin submucosal layer has been reported in most avian species [23] but missing in grey-backed shrike [22], while the tunica muscularis appeared broad with inner circular and outer longitudinal external muscle layer in avian species [18, 19, 2426]; these appeared similar to the findings of this study.…”
Section: Discussionmentioning
confidence: 99%